La relazionalità della proprietà collettiva. Commons e conservazione conviviale in Umbria, Italia - Michele Ravaioli (Revue de Géographie Alpine)
This article, within the field of mountain geographies, proposes a critical analysis of collective property, as a virtuous example of territorial governance, connecting property studies with the concepts of common and convivial conservation. Structuring a series of social relations based on mutual obligations and shared values between community members, within an active participation to the territorial management fostered by the collective status of land property, collective land structures represent peculiar commons that local communities use and take care of. In particular, collective land property and collective territorial management foster convivial conservation processes at the socioecological level, while the implementation of individual private property relations tends to promote uncontrolled phenomena of exploitation of resources and individualistic attitudes. The analysis of the case studies, that are the Umbrian Comunanze Agrarie of Massa Martana and Colpetrazzo, confirms the positive relationality of collective property, counterposed to the socialisation of people and spaces linked to the territorialisation of individual private property, as it allows the maintenance of common goods and spaces which guarantee a direct and democratic territorial governance able to contrast the present socio-environmental challenges.